(untitled) (International Journal of Islamic Business, 2025)
Islamic banking in Malaysia presents a unique case study of religious knowledge transfer through financial services in a multi-religious society. This study examined how Islamic banking serves as a channel for da’wah to non-Muslim communities by analyzing research published from 2012 to 2024. Through systematic literature review of 19 key studies, the research investigated non-Muslim engagement patterns, understanding of Islamic banking principles, the effectiveness of religious knowledge transfer, and the success factors for Islamic banking among non-Muslim customers. The findings revealed three distinct research clusters: customer perception studies (2012-2015), behavioral research (2016-2020), and knowledge transfer analysis (2021-2024). The results indicated that effective da’wah occurred primarily through indirect channels, with service quality and operational excellence serving as foundational elements for building trust and understanding. The study identified key success factors, including competitive pricing, technological accessibility, and culturally sensitive communication approaches. However, challenges persisted in the comprehension of Arabic terminology and complex Islamic financial concepts. The research made significant contributions by demonstrating how professional service delivery created natural pathways for religious understanding, highlighting the effectiveness of indirect knowledge transfer through business interactions, and providing evidence for the role of Islamic banking in fostering interfaith dialogue. These findings had important implications for Islamic financial institutions, policymakers, and researchers interested in the intersection of Islamic finance and cultural dialogue.